La Actuación Sugerente del Fiscal en el Procedimiento Abreviado Induce a la Autoincriminación Propia de la Concepción Inquisitiva Penal - Armijos Iñiguez, Karla Cecibel (2019)
The criminal process, raises two specific purposes that are the determination of the existence of a behavior that is typified in the law as a crime, and the establishment of the responsibility of a person in the commission of that violation, these purposes are intended to be verified in a fast way through the application of the abbreviated procedure, which is a special procedure contemplated in the General Organic Code of Processes. In this research work the abbreviated procedure is studied making a direct relation of the same with the right to nonincrimination recognized in the Constitution of the Republic as a guarantee of due process. The study compiles a conceptual, doctrinal and legal analysis that refers especially to the suggestive action of the prosecutor in relation to the acceptance of the defendant on the existence of the punishable conduct his participation in it and the suggested penalty, and the adoption of an inquisitive perspective within the abbreviated procedure, that is why it has been structured under the title: DOES THE SUGGESTED ACTION OF THE PROSECUTOR IN THE ABBREVIATED PROCEDURE INDUCE THE SELF-CRIMINATION OF THE CRIMINAL INQUISITIVE CONCEPTION?- The research is also based on results obtained through field work, which allows to dimension the characteristics of the problem in Ecuadorian society, and pays elements to conclude with the proposal of a legal proposal to reform the Comprehensive Organic Criminal Code, that contributes to better 5 delineate the regulations that regulate the abbreviated procedure as a mechanism to guarantee that it conforms to the constitutional precepts related to the right to due process, and guarantees the validity of all the rights that in the constitutional and procedural scope must recognize the person against whom the criminal prosecution is directed, that is, the defendant.